Evaluation of treatment schemes appropriate for wastewater reuse in Greece. (25th July 2006) - Andreadakis, Andreas; Mamais, Daniel; Gavalakis, Eugenia
The scope of this paper is to propose wastewater reuse quality criteria and treatment specifications for Greece, taking into consideration reuse priorities and secondary effluent characteristics. The proposed wastewater reclamation criteria and tertiary treatment schemes were evaluated in terms of feasibility and effectiveness through lab-scale experiments. The experimental data were processed by means of a stochastic statistical model employing Monte-Carlo simulation. The main scope of the stochastic approach was the generation of an enlarged set of data, based on the experimental results, defining the mathematical distribution of each parameter involved and the determination of relative probability distributions. Following this approach, it was concluded that the proposed standards are realistic and feasible. Restricted reuse can be achieved by moderate disinfection of secondary effluents. In the case of unrestricted reuse, the additional treatment required can be achieved at a moderate cost, through upgrading of the existing plants with tertiary treatment.